The Student Alcoholism Screening Test (SAST): Proposal and Exploration - Gaudin, K.; Johnson, Genevieve (Australian Association for Research in Education, 2011)
Problematic alcohol use among undergraduate university and college students is of international concern. Currently, there is no screening test specifically designed to indentify problematic alcohol use among undergraduate student populations. The proposed Student Alcoholism Screening Test (SAST) consists of 22 vignettes, each corresponding to an item on the Michigan Alcoholism Screening Test (MAST). SAST items specifically depict university student drinking behaviour (e.g., celebrating after examinations). In completing the SAST, students classify each vignette as reflecting either alcohol use or alcohol abuse. Choosing alcohol use indicates that the student is normalizing problematic alcohol consumption; choosing alcohol abuse indicates that the student recognizes the aversive nature of the drinking behaviour. Items classified as alcohol use receive a score of one while items classified as alcohol abuse receive a score of zero. The higher the SAST score, the more the student normalizes his/her drinking behaviour and, by inference, the more likely the student is to engage in problematic alcohol consumption. Three hundred seventy-one introductory psychology students, attending a Canadian university completed the MAST and the SAST via a controlled website. The vignette approach of the SAST may constitute an initial step toward a valid screening test for problematic alcohol use among university students.